Determinasi Penyebab Stunting dan Persepsi Sosial terhadap Resiliensi Keluarga di Kecamatan Gadingrejo Pasuruan - Baretha Yuanda; Desy Santi Rozakiyah (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
Stunting as a malnutrition problem signifies a gap in human development, soit is included in the 2nd SDGs indicator. The study aims to determine theinfluence of the causes of stunting and social perceptions on family resiliencein Gadingrejo Subdistrict, Pasuruan City because the prevalence of stuntingis 11.7% in 2023. The sample amounted to 80 families of stunted childrenrepresented by mothers. Data were collected through questionnaires, multipleregression analysis, and analyzed with Robert Putnam's social capital theory.A total of 373 children (February 2024) in Gadingrejo subdistrict werestunted. The analysis showed that the causes of stunting had a significanteffect on family resilience with a p value of 0.000, while social perceptions hadno significant effect on family resilience with a p value of 0.115. The causes ofstunting and social perceptions have a significant effect on family resiliencewith a p value of 0.000.